BALANCING RESPONSIBILITIES A COMPARATIVE STUDY OF ROLE OVERLOAD CHALLENGES AMONG EDUCATORS IN GOVERNMENT AND PRIVATE INSTITUTIONS IN BIHAR - kumari, Poonam (International Journal of Research -GRANTHAALAYAH, 2025)
This research presents a comprehensive comparative analysis of role overload challenges among educators in government and private institutions, unraveling nuanced dynamics in the educational landscape. The study, based on data from 304 participants in the Bihar Southwest region (Kaimur, Rohtas, Buxar, Bhojpur, and Patna), illuminates that both sectors contend with a moderate level of role overload challenges, with a slightly heightened prevalence among private school teachers. Through correlation analysis, intricate interconnections between specific dimensions of role overload emerge, providing valuable insights into the complexities of the teaching profession. The findings emphasize the necessity for targeted interventions, particularly in private schools, to clarify role expectations. Additionally, they serve as a foundation for further exploration into the contributing factors to these perceptions. Ultimately, this study enhances our understanding of organizational stressors in education, underscoring the significance of addressing role-related challenges for the well-being of teachers and the effectiveness of educational institutions.